Cross-Border Multi-Stakeholder Platform of Tana-Kipini-Laga Badana Bushland and Seascape, Kenya-Somali Border - Malesu, M.; Koech, G. (CIFOR-ICRAF, 2021)
The Horn of Africa, particularly the eastern Africa region, covering the coastal strip of Kenya, Somalia Ethiopia, Eritrea, and Djibouti have a historical context characterised by conflict and insecurity. Periodic mass migration and break down of law and order has weakened the grassroots’ institutional fabric, thus threatening not only peoples’ livelihoods but also the sustainability of natural systems. In line with the state of the region, the Biodiversity Management Program (BMP) of the Intergovernmental Authority on Development (IGAD) of the Horn of Africa was established to promote sustainable biodiversity conservation in the Tana-Kipini-Laga Badana Bushland and Seascape---a cross-border landscape of the extreme southern part of Somalia and north-eastern Kenya.